2004
DOI: 10.2105/ajph.94.5.738
|View full text |Cite
|
Sign up to set email alerts
|

Swimmer’s Itch: Incidence and Risk Factors

Abstract: Swimmer's itch (cercarial dermatitis) affects people engaged in open-water activities. We report incidence and risk factors for a US lake. Water exposures and swimmer's itch experience were reported daily for riparian household residents and guests at Douglas Lake, Michigan, in July 2000. Incidence of swimmer's itch was 6.8 episodes per 100 water exposure days. Positive risks were (1) exposures in shallow water and in areas with onshore winds and (2) more days of lake use in July. Further epidemiological studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 17 publications
0
42
0
2
Order By: Relevance
“…Cercarial dermatitis develops as a result of sensitization of the human immune system (232,260), and repeated exposures to cercariae influence the occurrence and intensity of subsequent infections. For example, longer exposure in water increases cercarial penetration via frequent water visits and more time spent in shallow water (4,(304)(305)(306). While gender does not influence the risk of infection (4,304,305,307), some studies found a higher risk among children of less than 15 years of age, since they tend to spend more time in shallow water (280,308,309).…”
Section: Recreational Activities and Cercarial Dermatitismentioning
confidence: 99%
See 4 more Smart Citations
“…Cercarial dermatitis develops as a result of sensitization of the human immune system (232,260), and repeated exposures to cercariae influence the occurrence and intensity of subsequent infections. For example, longer exposure in water increases cercarial penetration via frequent water visits and more time spent in shallow water (4,(304)(305)(306). While gender does not influence the risk of infection (4,304,305,307), some studies found a higher risk among children of less than 15 years of age, since they tend to spend more time in shallow water (280,308,309).…”
Section: Recreational Activities and Cercarial Dermatitismentioning
confidence: 99%
“…For example, longer exposure in water increases cercarial penetration via frequent water visits and more time spent in shallow water (4,(304)(305)(306). While gender does not influence the risk of infection (4,304,305,307), some studies found a higher risk among children of less than 15 years of age, since they tend to spend more time in shallow water (280,308,309). There are rare cases of nonsensitive individuals that may be due to host desensitization (310) or individual nonsusceptibility/nonattractivity to cercariae (4,311).…”
Section: Recreational Activities and Cercarial Dermatitismentioning
confidence: 99%
See 3 more Smart Citations